Silverlight 2 Visual Essentials - MacDonald, Matthew (Springer, 2017)
Silverlight is a lightweight browser plug–in that frees your code from the traditional confines of the browser. It is a rules–changing, groundbreaking technology that allows you to run rich client applications right inside the browser. Even more impressively, it is able to host true .NET applications in non–Microsoft browsers (like Firefox) and on non–Microsoft platforms (like Mac OS X).